Keynesian and Austrian Perspectives on Crisis, Shock Adjustment, Exchange Rate Regime and (Long-Term) Growth - Mathilde Maurel; Gunther Schnabl (Graduiertenkolleg 'Konstitutionelle Grundlagen globalisierter Finanzmärkte - Stabilität und Wandel', 2011)
The 2010 European debt crisis has revived the discussion concerning the optimum adjustment strategy in the face of asymmetric shocks. Whereas Mundell's (1961) seminal theory on optimum currency areas suggests depreciation in the face of crisis, the most recent emergence of competitive depreciations, competitive interest rate cuts or currency wars questions the exchange rate as an adjustment tool to asymmetric economic development. This paper approaches the question from a theoretical perspective by confronting exchange rate based adjustment with crisis adjustment via price and wage cuts. Econometric estimations yield a negative impact of exchange rate flexibility/volatility on growth, which is found to be particularly strong for countries with asymmetric business cycles and during recessions. Based on these findings we support a further enlargement of the European Monetary Union and recommend more exchange rate stability for the rest of the world.
urn:nbn:de:gbv:27-20131118-113946-9
Keywords: 330; Shock Adjustment; Exchange Rate Regime; Growth; Wechselkurssystem; Makroökonomischer Einfluss; Wirtschaftswachstum; Wirtschaftskrise; Schock; Wirtschaftspolitik; Keynesianismus; Österreichische Schule; Wirtschaftliche Anpassung; Theorie; Eurozone